Red nose experiences – health and the aging body (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The text that begins here deals with the experiences with the figure of the clown in workshops carried out by the Circo em Contextos project, together with the Open University of the Third Age (UATI), in the year 2022. It aims to report and discuss the pedagogy of clowns and their relationships with health and Physical Education in a group of elderly women, based on sharing memories and bodily experiences with clown games. The weekly meetings were attended by 18 women members of the UATI, aged between 55 and 90 years old. Thirteen classes of 45 minutes each were held, addressing knowledge about clowns and expressive games with an emphasis on clowning. Bearing in mind that the clown builds with what is ridiculous, unusual, with the imperfections inherent to the human condition, the work carried out enabled the participating women to have a new attitude towards the aging body, facing its weaknesses, re-elaborating them as a power.
Keywords: Clown; Body education; Elderly women